2000
DOI: 10.1093/oxfordjournals.bja.a013448
|View full text |Cite
|
Sign up to set email alerts
|

Caudal clonidine for postoperative analgesia in adults

Abstract: We have assessed the analgesic efficacy and side effects of caudally administered clonidine in a prospective, randomized, double-blind, placebo-controlled study. We studied 64 adult patients undergoing elective haemorrhoidectomy. Caudal block was performed in all patients using a mixture of 0.5% bupivacaine 35 mg with 2% lidocaine 140 mg and epinephrine 5 micrograms ml-1. Patients were allocated randomly to one of two groups. Clonidine 75 micrograms was added in group C and saline 1 ml in group S. Median time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 2 publications
0
17
0
1
Order By: Relevance
“…The bradycardia occurred in seven of 32 patients in the group that used clonidine, but there were no changes in the average blood pressure 24 .…”
Section: Moreover the Number Of Patients In The Experimentsmentioning
confidence: 88%
“…The bradycardia occurred in seven of 32 patients in the group that used clonidine, but there were no changes in the average blood pressure 24 .…”
Section: Moreover the Number Of Patients In The Experimentsmentioning
confidence: 88%
“…In a study with patients submitted to hemorrhoidectomy under caudal epidural anesthesia, it has been observed that mean time for first analgesic request was longer in the group receiving clonidine and local anesthetics as compared to the group receiving saline and local anesthetics 13 . In patients submitted to total hip replacement, mean time for first analgesic request was longer in the group receiving clonidine and levobupivacaine as compared to those receiving local epidural anesthetics alone 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Estudo realizado em pacientes submetidos à hemorroidectomia, sob anestesia peridural caudal, constatou que o tempo médio para que ocorresse solicitação da primeira dose de analgésico foi maior no grupo em que foram injetados clonidina e anestésicos locais, quando comparado ao grupo em que foram administrados solução fisiológica e anestésicos locais 13 . Nos pacientes submetidos à prótese total de quadril, o tempo médio até a primeira solicitação de analgésicos foi maior no grupo em que foram injetados clonidina e levobupivacaína do que no grupo que recebeu apenas o anestésico local no espaço peridural 6 .…”
Section: Discussionunclassified
“…On hemorroidectomy, under caudal blockage, it was associated with a mixture of bupivacaine, lidocaine and epinefrine, caused more prolonged analgesia than the saline solution added to such mixture 21 . On proctologic surgeries, especially hemorroidectomy, the clonidine associated with lidocaine and fentanil, on subarachnoid anesthesia, prolonged the time of analgesia, reducing the intensity of pain, with minimum side effects 22 .…”
Section: Discussionmentioning
confidence: 99%